2017
DOI: 10.1111/1753-6405.12654
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the barriers to driver licensing for Aboriginal people in New South Wales and South Australia

Abstract: Objective: Low rates of driver licensing have been linked to increased risk of transport-related injury, and reduced access to health services, employment and educational opportunities in the Aboriginal population. This paper reports on how barriers to obtaining a driver licence are being addressed in four Aboriginal communities in New South Wales and South Australia.Methods: Qualitative data were collected over a four-month period in 2013. Interviews with Aboriginal and non-Aboriginal stakeholders (n=31) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…One key way forward borne out of the research is the need to address perceived hopelessness among Indigenous people through improvements to the licensing process, leading to better life circumstances [14]. This requires integrating road safety into other policy agendas (employment) and building on community strengths and learning styles as an educational strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One key way forward borne out of the research is the need to address perceived hopelessness among Indigenous people through improvements to the licensing process, leading to better life circumstances [14]. This requires integrating road safety into other policy agendas (employment) and building on community strengths and learning styles as an educational strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research to suggest that the crash profile associated with road trauma in Indigenous communities is related to an array of social and environmental factors including 'transport disadvantage' [6,10], reduced access to licensing programs and culturally suitable road safety education [11][12][13][14] and reluctance to fully utilise organised health and rehabilitation services [15,16]. The need to develop appropriate and accessible pathways to obtaining and maintaining a driver's licence in Indigenous communities, with related road safety benefits, is gaining national momentum [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high number of Aboriginal and Torres Strait Islander people incarcerated for regulatory road-related offences it seems likely that traditional enforcement-based initiatives are likely to result in increased numbers of people with prohibitive fines, potentially leading to great inequality in incarceration 33. Alternative approaches should therefore be considered, potentially including community-owned and led transport, licensing and restraint programmes 17 34 35. Codesign and development of programmes that involve and engage Aboriginal and Torres Strait Islander people to address risk factors and community priorities are vital to sustainable and effective programmes.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional survey of clients (n=625) attending four ACCHS in two Australian states with a geographic spread across urban, regional and remote locations: Redfern (urban) and Griffith (regional) in NSW; Port Lincoln (remote) and Ceduna (very remote) in SA. This survey formed part of a larger mixed methods study for which detailed methods have been reported previously 16 17. The study was overseen by a steering committee, comprising the investigators, representatives from the Aboriginal Health and Medical Research Council (AH&MRC) of NSW, the Aboriginal Health Council of South Australia (AHCSA) and representatives from ACCHS Aboriginal and Torres Strait Islander policy officers from the transport authorities in each state.…”
Section: Methodsmentioning
confidence: 99%
“…Of concern, is the over-representation of Aboriginal adolescents in the juvenile justice system; in 2016–2017, 50% of the adolescents aged 10–17 in the juvenile justice system were Aboriginal; with the proportion higher in detention (59% of the young people aged 10–17 years10). Similarly, given high rates of road deaths in young Aboriginal people, and evidence of significant barriers to driver licensing and implications for employment,11 12 identification of factors associated with positive social trajectories will enable implementation of support services to improve outcomes for Aboriginal adolescents.…”
Section: Introductionmentioning
confidence: 99%